Propozycja Programu Całościowej Zintegrowanej Aktywności Dzieci dla dzieci jąkających się i ich rodzin – badanie pilotażowe - Jastrzębowska-Jasińska, Aleksandra (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article analyzes the pilot study of the new original Holistic Integrated Children’s Activity Program for stuttering children and their families. It presents the basics and the assumptions of the program and the therapeutic interactions. The article also shows the program’s differences from and similarities to the therapeutic methods applied to children with early childhood stuttering, including the author’s experience in therapy, indicating the novelty of the described program. An analysis of the results of the first test of the program’s effectiveness was conducted, indicating its positive effects in the field of stuttering therapy and support of mental resilience in pre-school children.